Role of Government in the Economic Valorization of Innovation and University Research: The Case of Morocco - Ouahraoui, Fatima; Soudi, Nada (European Scientific Journal, ESJ, 2020)
The development of university researches and the economic valorization of innovation for industries and companies are still nourishing a scientific debate. It is perceived today as a priority and as an axis of investment of the States. They were involved in the ecosystem to ensure a "win-win" cooperation between the two partners and explore a triptych "model 2 " linking the State, the university, and companies. This paper focuses on working on the Moroccan experience and the role of the national government in the implementation of this model of cooperation. After an exhaustive review of all organizations related to innovation in Morocco, three models illustrate the cooperation of the three stakeholders (Industry, State and University) as a Triple Helix models. This involves innovation centers, clusters, and incubators. Following the results of the theoretical part, a quantitative study was conducted based on targeted survey. The objective is to demonstrate, through the answers, the level of involvement and the role of the Moroccan government in the realization of the triple helix model. Findings of this review revealed that the Triple Helix model is highly elucidated in the "Centers of Innovation" since the budget including the governance, and this model implies the three stakeholders. The clusters are more linked to the industries while the incubators are more linked to the universities.